Strategi Pengelolaan Jamiyah Dirosatul Qur’an dalam Meningkatkan Partisipasi dan Keaktifan Anggota di Desa Gemurung, Gedangan, Sidoarjo - Alvina Zahroh; Wahyu Eko Pujianto (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Jamiyah Dirosatul Qur'an, situated in Gemurung Village, Gedangan, Sidoarjo, is a community-based religious organization currently grappling with weak member participation and engagement in its weekly routine activities. In response to this issue, the present study sets out to explore the organization's management strategy in greater depth, focusing on three central dimensions, namely leadership, activity management, and financial transparency, along with how these three dimensions interact in shaping member participation and engagement. A qualitative approach with a case study design underpins this research. Primary data were gathered through in-depth interviews involving three informants, the chairperson together with two members, supported by participatory observation, with the resulting data examined through an interactive analysis model. The results indicate that the limited degree of personal communication initiated by the management leaves some members feeling disregarded, leading their attendance to be shaped more by incidental circumstances than by a genuine sense of belonging to the organization. With respect to activity management, the repetitive nature of the weekly routine has bred fatigue among members, whereas the occasional and unscheduled religious tourism activities have, somewhat paradoxically, proven far more successful in drawing broader participation. Turning to financial transparency, while the basic fee mechanism is collectively understood, detailed information regarding the use of funds beyond the portion allocated to the hosting member is never formally communicated, a gap that has gradually bred suspicion among members. Taken together, these findings lead to the conclusion that the three dimensions are not independent of one another but rather deeply interconnected, requiring integrated management to sustain member participation and engagement over the long term.